Computationally efficient optimal power allocation algorithm for multicarrier communication systems - Krongold, B.S.; Ramchandran, K.; Jones, D.L. (1998 IEEE International Conference on Communications, 1998)
We present an optimal, efficient power allocation algorithm for discrete multitone modulation (DMT). Using efficient lookup table searches and a Lagrange multiplier bisection search, our algorithm converges much faster to the optimal solution than existing techniques and can replace the use of suboptimal methods because of its low computational complexity. A fast algorithm is developed and a pseudocode is provided.